Perancangan Game Story “Inner Threads” Sebagai Media Edukasi Kesehatan Mental Pada Generasi Muda Di Indonesia - Laila; Ahmad Khoirul Anwar; Yudi Wibowo (Universitas Sahid Surakarta, 2026)
ABSTRACTMental health is a crucial aspect of individual well-being, yet it is a pressing concernamong Indonesia's younger generation. Data from the 2022 I-NAMHS shows that34.9% of adolescents experience mental health issues, with 5.5% diagnosed with amental disorder. Studies also indicate that cases of mental disorders, particularlyanxiety and depression, peak in early adulthood (21-23 years). However, it is still only2.6% of adolescents who access services. Globally, the WHO identifies adolescents asbeing at high risk for mental disorders, with depression being the leading cause ofdisability and suicide the leading cause of death among those aged 15-29. In responseto this gap, this project developed